(3eYhfI GdaGQV hcaGjI GdaQGFVs - (3eMeO Hf Ydj Hf YKeGf Hf Ydj GdcQGLcj, CHh GdaJMs ((3eMeO GdSeGhi s)
(3ChdgG (B:s
(3gPG cJGH fPcQ ajg aQGFV GdhGQK hGSJNQGL egGege Ydi GdUMI Ohf GdEfcSGQ s
(3BNQgG (B:s
(3ShGA bJdg YekG Ch NWkG Gh cJH CUMGHfG JJVef Efg jhQK EPG bJdkg s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B515s
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B- (3GdfLa (B(14/298) s
Keywords: (3Yde GdaQGFVs